Commentary: Periodontal Treatment and Inflammation in Diabetes: Association or Causation?. Issue 10 (1st October 2016) - Merchant, Anwar T.; Josey, Michele J.
Abstract : The causal effect of periodontal treatment on systemic outcomes is unclear because even randomized controlled trials (RCTs) have conflicting results. Two models are proposed to explain the apparently conflicting findings from RCTs evaluating the effect of periodontal treatment on inflammation and systemic outcomes among individuals with type 2 diabetes.